If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(r + -3) = 0 Reorder the terms: 6(-3 + r) = 0 (-3 * 6 + r * 6) = 0 (-18 + 6r) = 0 Solving -18 + 6r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 6r = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6r = 0 + 18 6r = 0 + 18 Combine like terms: 0 + 18 = 18 6r = 18 Divide each side by '6'. r = 3 Simplifying r = 3
| T=5y | | 10-5x-x^2=0 | | 5x+x+180=360 | | -6(-4xy)= | | .7(5x+3)=1.1-(x+3) | | .7(6x+2)=1.1-(x+6) | | -6+11r+10k-4r-4k-9= | | 7(5-2a/3) | | iz^4+4+4i=0 | | 200-0.9x=50+10x | | (6y-4)y+3=0 | | 2(y+8)=3(y-4) | | 64+225=x | | 1/2-x/4=17/8 | | 933x=100 | | 7024x=100 | | 2+8x=-40+x | | 4y^2=-28y | | X=x-1*x-9 | | 100x+60y=6000 | | x-x+14=0 | | 6x=2+40 | | 200x-20=100x+60 | | 200n^2+299n-2569000=0 | | 59x+22.5=105-25x | | 14-15g=4 | | -5x-64=-50x+344 | | 2/3m-1/5=5/7 | | 120x+42=100-24x | | (2x+6)(2x+8)=120 | | 37k-32=32 | | (5x^2+8x+5)-(2x^2-3x+2)= |